Establishment and characterization of NCC-ssRMS1-C1: a novel patient-derived spindle-cell/sclerosing rhabdomyosarcoma cell line - Yoshimatsu, Yuki; Noguchi, Rei; Tsuchiya, Ryuto; Sei, Akane; Sugaya, Jun; Iwata, Shintaro; Sugiyama, Masanaka; Yoshida, Akihiko; Kawai, Akira; Kondo, Tadashi (Human cell : official journal of Human Cell Research Society, 2020)
Spindle-cell/sclerosing rhabdomyosarcoma (ssRMS) is a rare subtype of rhabdomyosarcoma, characterized by unique pathological features. Although distinctive molecular backgrounds such as frequent mutations in MyoD1 have been reported, optimized therapy has not been fully developed, and further investigations are required. Patient-derived cancer models are critical tools for basic and pre-clinical studies. However, there is no model for ssRMS. Thus, this study aimed to develop a novel cell line from the tumor tissue of a patient with ssRMS. Using surgically resected tissue, we successfully established this cell line, named NCC-ssRMS1-C1. These cells exhibited spindle-shape morphology, consistent with the pathological observations of the original tumor tissue. Genetic studies demonstrated that NCC-ssRMS1-C1 cells retained original copy number alterations and the typical point mutation in MyoD1 . Malignant phenotypes such as proliferation, spheroid formation, and invasion were confirmed in vitro by studying NCC-ssRMS1-C1 cells. Upon screening an anti-cancer agent library, sensitivity to conventional chemotherapeutic agents such as actinomycin D was revealed. We conclude that the NCC-ssRMS1-C1 cell line will be a useful resource for basic and pre-clinical studies.